Pouring Oil on Fire : Interest Deductibility and Corporate Debt - Dallari, Pietro; End, Nicolas; Miryugin, Fedor; Tieman, Alexander (Washington, D.C. : International Monetary Fund, 2018)
This paper investigates the role of tax incentives towards debt finance in the buildup of leverage in the nonfinancial corporate (NFC) sector, using a large firm-level dataset. We find that so-called debt bias is a significant driver of leverage, for both small and medium-sized enterprises and larger firms, with its effect accounting for about a quarter of leverage. The strength of this effect differs with firm size, the availability of collateral, income and income volatility, cash flow, and capital intensity. We conclude that leveling the playing field between debt and equity finance through tax policy reform would decrease NFC leverage, reducing economic risks posited by leverage.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet